2013
DOI: 10.4028/www.scientific.net/amr.634-638.970
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Preparation of Azetidin-3-Ones from Propargylic Alcohols by Gold-Catalysis

Abstract: Azetidin-3-ones are important heterocycles in organic synthesis and pharmaceutical chemistry. With gold-catalyzed alkyne intermolecular oxidation, these versatile heterocycles can be prepared in three steps from readily available propargylic alcohols with high efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It was later shown that several other sulfonyl-protecting groups were tolerated in this reaction. 784 Notably, the tert -butanesulfinamide group allowed preparation of enantioenriched products by employing the chemistry of Ellman. 785 …”
Section: Construction Of 4-membered Rings Catalyzed By Goldmentioning
confidence: 99%
See 2 more Smart Citations
“…It was later shown that several other sulfonyl-protecting groups were tolerated in this reaction. 784 Notably, the tert -butanesulfinamide group allowed preparation of enantioenriched products by employing the chemistry of Ellman. 785 …”
Section: Construction Of 4-membered Rings Catalyzed By Goldmentioning
confidence: 99%
“…It was later shown that several other sulfonylprotecting groups were tolerated in this reaction. 784 Notably, the tert-butanesulfinamide group allowed preparation of enantioenriched products by employing the chemistry of Ellman. 785 Although the formation of oxetan-3-ones and thietane-3-ones under oxidative gold catalysis has been sporadically re-ported, 786,787 the only gold-catalyzed preparative methods for the synthesis of heteroatom-containing 4-membered rings remain the two protocols developed by the group of Zhang.…”
Section: Synthesis Of Heteroatom-containing 4-membered Ringsmentioning
confidence: 99%
See 1 more Smart Citation